2016
DOI: 10.3892/or.2016.4908
|View full text |Cite
|
Sign up to set email alerts
|

Insights into roles of the miR-1, -133 and -206 family in gastric cancer (Review)

Abstract: Gastric cancer (GC) remains the third most common cause of cancer deaths worldwide and carries a high rate of metastatic risk contributing to the main cause of treatment failure. An accumulation of data has resulted in a better understanding of the molecular network of GC, however, gaps still exist between the unique bio-resources and clinical application. MicroRNAs are an important part of non-coding RNAs and behave as major regulators of tumour biology, alongside their well-known roles as intrinsic factors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 94 publications
0
22
0
Order By: Relevance
“…It can interact with miRNA to participate in the expression of the target gene. A large number of studies have shown that miR-21 is highly expressed in gastric cancer, and its expression is associated with the invasion and metastasis of the tumor [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…It can interact with miRNA to participate in the expression of the target gene. A large number of studies have shown that miR-21 is highly expressed in gastric cancer, and its expression is associated with the invasion and metastasis of the tumor [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…8,11,12 For instance, Wu et al 13 indicated that miR-429 can attenuate the migratory and invasive ability of BC cells. Another study conducted by Xie et al 10 demonstrated that miR-1 is associated with the viability, migration, and invasion of gastric cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…It binds to the 3′ untranslated region (UTR) of target messenger RNAs (mRNAs) and affects the corresponding transcription process. 4,10 The aberrant expression of miRs is often observed in various human malignancies and growing processes, suggesting that miRs play a pivotal role in the metastasis and invasion of carcinoma (mostly working as oncogene suppressors). 8,11,12 For instance, Wu et al 13 indicated that miR-429 can attenuate the migratory and invasive ability of BC cells.…”
Section: Introductionmentioning
confidence: 99%
“…Some miRNAs, regarded as potential therapeutic targets, have also had been reviewed elsewhere. [94][95][96] Our review focused more on discussing miRNAs that are more promising for clinical use. We believe that miRNAs that have an effect on GC treatment (including chemotherapy, targeted therapy, immunotherapy, and others) could also become core targets in microRNA-based therapies.…”
Section: Microrna-based Other Therapiesmentioning
confidence: 99%